2013
DOI: 10.1504/wrstsd.2013.050788
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics modelling of UR-UVGI lamp effectiveness to promote disinfection of airborne microorganisms

Abstract: This paper focuses on using computational fluid dynamics (CFD) modelling methods to study the effectiveness of upper-room ultraviolet germicidal irradiation (UR-UVGI) lamps in healthcare facilities. This work develops and uses simplifications for boundary conditions in CFD, while details of UR-UVGI lamps and microorganism characteristics were obtained from existing experimental studies. Three approximation methods were developed to implement the effects of UR-UVGI lamps on microorganism dispersion patterns rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The Eulerian method has been widely applied to performance predictions of upper room UVGI systems in a steady indoor environment in previous studies [6,18]. The method is based on the notion that microorganisms occupy a certain fraction of the air volume.…”
Section: Eulerian Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Eulerian method has been widely applied to performance predictions of upper room UVGI systems in a steady indoor environment in previous studies [6,18]. The method is based on the notion that microorganisms occupy a certain fraction of the air volume.…”
Section: Eulerian Methodsmentioning
confidence: 99%
“…To repair this, we wrote a user-defined function to restrict the fluence rate only within the irradiated zone (Z ¼ 2.13e2.85 m) after import. The effect of fluence rate modeling representation on the predictions of UVGI efficiency was studied by Heidarinejad and Srebric [18], who found that a manual, multi-volume segregation of the fluence rate was sufficiently accurate. The direct import, used here, offers better detail and saves the effort for manually partitioning the irradiated zone.…”
Section: Cfd Simulation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the literature review, this model can well predict the transport and dispersion of particles and bioaerosols in indoor environments [19,20]. Pathogen-carrying droplets are simulated as inert spherical particles, 2.5 mm in diameter, with density of 1000 kg/m 3 .…”
Section: Bacteria Transport Simulationmentioning
confidence: 99%
“…Hathway et al [19] evaluated using CFD modeling the risk from the transport of infectious bioaerosols in spaces with conventional air conditioning. Heidarinijad and Srebric [20] presented different CFD modeling methods of upper room UVGI effectiveness. The obtained CFD results were then compared with existing experimental studies.…”
Section: Introductionmentioning
confidence: 99%